Natural history of inflammatory and non-inflammatory dry eye in thyroid eye disease. (3rd September 2021) - Lo, Christopher; Yang, Michael; Rootman, Daniel
ABSTRACT: Purpose: The purpose is to understand the natural history and physical findings in thyroid eye disease (TED) patients with severe dry eye symptoms (DES). Methods: Prospective cohort study, studying DES in TED patients over two years. Baseline data included clinical activity score (CAS), time since disease onset, punctate epithelial erosions (PEE), lagophthalmos, superior limbic keratoconjunctivitis (SLK), and marginal reflex distance 1 (MRD1). Ocular Surface Disease Index (OSDI) was utilized to measure symptomatology and scores > 33 (severe) were the primary outcome measure. Multivariate logistic regression was performed on two groups (<9 months, >9 months) to assess if variables change in early versus late disease. Results: 88 met the inclusion criteria. 80.7% (n = 71) were female. There were 42 patients in the group with onset of symptoms under nine months and 46 patients over nine months. Mean CAS score was greater under nine months (2.45) than over nine months (1.29) ( p < .05). In the multivariate logistic regression for the group presenting with symptoms under nine months, CAS was the only significant predictor of severe OSDI. Every increase in CAS of one yielded a 2.0x increased risk of severe OSDI. For the patients over nine months from onset, PEE was the significant predictor of severe OSDI. PEE was associated with a 5.9x increased risk of severe OSDI. Conclusions: Severe DES correlate with inflammatory features within the first nine months. Afterward, presence of PEE became more important. DES in TED tends to be a manifestation of orbital inflammation early in disease and exposure later.